Physiological quality of cowpea bean (Vigna unguiculata L. Walp.) seed by the electrical conductivity and germination testing - Araméndiz-Tatis, Hermes; Cardona-Ayala, Carlos; Espitia-Camacho, Miguel; Peña-Salgado, Luisa; Doria-Pérez, Tatiana (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
Cowpea is the main legume of the Colombian Caribbean. It is cultivated by small producers, who use seeds from their own crops, stored under uncontrolled environmental conditions. The objective of this research was to evaluate the physiological quality of the seeds of five cowpea cultivars stored for 8-10 years. For the electrical conductivity test, six experiments were carried out (0, 4, 8, 12, 16, and 20 hours of imbibition), using a completely randomized design with five replicates of 50 seeds each per treatment. For the germination test in the greenhouse, a randomized complete block design was used with four repetitions of 50 seeds each per treatment. The results indicate that both methods were efficient in identifying reduction of seed viability due to storage effects, with the differential response of cultivars being due to their genetics. The most affected genotypes were L-026 and C-Tierralta, because they showed a greater amount of leachate 107.19±11.81 and 108.87±8.57 µS cm-1 g-1, respectively at 16 h of imbibition, lower percentage of germination and rate of germination speed index.